The Effect of Cash Flow, Tax Avoidance, Growth Opportunity, and Net Working Capital on Cash Holding in the Financial Sector Listed on the Indonesia Stock Exchange (IDX) in 2019-2021 - Widiyarti, Widiyarti; Murdijaningsih, Tjahjani; Octisari, Sully Kemala (Journal of Business and Management Review, 2023)
This study aims to examine the partial significance of the effect of cash flow, tax avoidance, growth opportunity, and net working capital on cash holding in financial sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The population in this study were 99 financial sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling and obtained 61 companies. The analytical tool used in this research is panel data regression with the help of Eviews 10 statistics. The results showed that the effect of cash flow and growth opportunity had a positive and significant effect. While tax avoidance and net working capital have a negative and significant effect. The implication of this research is that to increase optimal cash holding, companies must pay attention to cash flow and growth opportunities because the results of the study show that they have a positive and significant effect on cash holding. This research contributes to the development of further research related to cash holding. The limited number of samples with limited research objects as well